COMBINATION OF ACE INHIBITOR WITH AGONIST OF I1 -IMIDAZOLINE RECEPTORS: NEW OPPORTUNITIES FOR ANTIHYPERTENSIVE THERAPY - S. V. Nedogoda (Российский кардиологический журнал, 2016)
The number of patients with metabolic syndrome and obesity is continuously increasing. Specifics of arterial hypertension in obesity is related to activation of renin-angiotensin-aldosterone system and sympathetic system, inflammation, early and prominent target organs damage, which is significant to be considered in rational antihypertensive therapy. Also, combination treatment should positively influence the bodyweight of a patient, improve insuline sensitivity of the tissues and metabolic profile (carbohydrate and lipid metabolism). One of the solutions for this is prescription of combination treatment by perindopril and moxonidine, which is synergetic for the target level of blood pressure achievement, protection of organs, suppression of sympathic system and insulin resistance.